The Influence of Artificial Intelligence Development on the Transformation of Private Universities: Case Study at Nahdlatul Ulama University Cirebon - Kohar, Abdul (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama’ah, 2025)
Research objectives. The development of artificial intelligence (AI) technology has become a major driver of transformation in various sectors, including higher education. This study aims to analyze the impact of AI implementation on institutional transformation at Nahdlatul Ulama University Cirebon as one of the private universities in Indonesia. Materials and methods. Using a qualitative descriptive approach, data were collected through in-depth interviews, participant observation, and documentation studies of academic systems and technology-based campus services. Results. The results of the study indicate that AI plays an important role in improving the efficiency of academic administration services, personalizing learning, and supporting data-based decision-making. However, there are still various challenges such as limited HR competency, uneven technological infrastructure, and the unavailability of ethical guidelines for the use of AI. Conclusion. This study confirms that AI-based transformation requires a strategic and inclusive approach in order to optimize the potential of AI sustainably in the private university environment.